Nest site selection and digging attempts of green turtles (Chelonia mydas, family Cheloniidae) at Pantai Kerachut and Telok Kampi, Penang Island, Peninsular Malaysia - Sarahaizad, M.S.; Shahrul Anuar, M.S.; Mansor, Y. (Penerbit Universiti Kebangsaan Malaysia, 2012)
The Pantai Kerachut Turtle Conservation Centre represents the centre of research study of sea turtles in Penang Island. For the study of nest site selection, 37 nests were located between 10-40m from the high tide line at Pantai Kerachut than at the same distance (10-40 m) from high tide line at Telok Kampi. It is believed that 3 nests were located at a distance of 0-10m from the high tide line because the location is near to the water’s edge and the sand which is exposed to high relative humidity (1.6-1.7%) is unsuitable for Green Turtles Chelonia mydas to lay eggs. At locations beyond 40 m from the high tide line, the sand is too dry (30-31ºC) and the low relative humidity (0.6-0.7%) makes it unsuitable for turtles to dig nests. For the study of nest site selection in relation to vegetation zone, more nests were distributed within the vegetation zone at both beaches. Green Turtles prefer to land and nest within the vegetation of Merambong (Scaevola taccada) due to the shelter, protection, and dark environment. At the open beach, Green Turtles are exposed to disturbance from feral dogs, while grass areas provide less shelter than Merambong trees.